Effect of cryolite as sintering-aids on the structure and conductivity of Li0.25La0.25NbO3 ceramic solid electrolytes for solid state lithium batteries - Shihang Hu; Jie Chang; Yazhou Kong; Shuai Zhang; Chengcheng Cai; Zexiong Wang; Weiwei Hu; Guang Hu; Kailong Zhang; Jiadong Zhang; Kun Hong (Next Materials)
The sintering temperature of oxidizing solid electrolytes is usually much higher than that of electrode materials. This study introduced cryolite into Li0.25La0.25NbO3 ceramic matrix as a sintering additive to reduce its sintering temperature and improve the electrical properties. The properties of Li0.25La0.25NbO3–cryolite composites were measured by XRD, SEM, AC-impedance, and DC-polarization. The results show that the addition of cryolite can effectively promote sintering for Li0.25La0.25NbO3 ceramic and the performance of Li0.25La0.25NbO3 ceramic is improved when sintered at only 1050 °C. The total ionic conductivity reached 1.37 × 10−5 S cm−1, which is comparable to samples without cryolite that sintered at 1100 °C. The contribution of electronic conductivity in cryolite-modified Li0.25La0.25NbO3 ceramic to the total conductivity is negligible. A feasible scheme for decreasing sintering temperature and improving sintering and electrical property for Li0.25La0.25NbO3 ceramic solid electrolytes is provided in this work.